Cost-effectiveness of on-site musculoskeletal ultrasound in an outpatient rheumatology clinic. (30th October 2020) - Acebes, Carlos; Rubio, Laura; Román, Almudena; Herrero, Antonio; Arcos, Javier
Abstract: Objective: To evaluate the impact of the routine use of musculoskeletal ultrasound (MSUS) in rheumatology clinics by comparing one clinic with on-site MSUS (REU 1) and four clinics without this resource, which need to refer patients for the MSUS exams (REU 2–5). Methods: The electronic medical records of all new patients at five rheumatology clinics during a 12-month period were reviewed. The impact of MSUS was analysed by comparing the percentage of direct discharges of patients from the different clinics, as an outcome of effectiveness, and the number and cost of radiology referrals for imaging exams (MSUS and MRI), as an outcome of cost-saving. Results: The medical records of 4923 patients were included in the study, distributed as follows: REU 1, 1464 (29.7%); REU 2, 1042 (21.2%); REU 3, 1089 (22.1%); REU 4, 579 (11.8%); and REU 5, 749 (15.2%). There were more direct discharges from REU 1 (34.4%) than from REU 2–5 (15.6%) ( P <0.001). REU 1 made radiological referrals for X-rays, MRIs or MSUS exams in 773 (52.8%) patients, compared with 2626 (75.9%) patients in REU 2–5 ( P <0.001). An estimation of costs for the clinical assessment of 1000 new patients revealed a cost-saving in REU 1 of €21 413 in MSUS and of €877 in MRI exams. Conclusion: The implementation of on-site MSUS in a new-patient rheumatology clinic is cost-effective, facilitating the direct discharge of patients and reducing the number and cost of radiological referrals for imaging exams.